Biodegradation of high di-(2-Ethylhexyl) phthalate (DEHP) concentration by food waste composting and its toxicity assessment using seed germination test. (1st January 2023) - Tran, Huu-Tuan; Lin, Chitsan; Lam, Su Shiung; Le, Thi Hieu; Hoang, Hong-Giang; Bui, Xuan-Thanh; Rene, Eldon R.; Chen, Po Han
Abstract: Di-(2-ethylhexyl) phthalate (DEHP), a plasticizer derived from phthalate ester, is used as an additive in industrial products such as plastics, paints, and medical devices. However, DEHP is known as an endocrine-disrupting chemical, causing cancers and adverse effects on human health. This study evaluated DEHP biodegradation efficiency via food waste composting during 35 days of incubation. At high DEHP concentrations (2167 mg kg −1 ) in food waste compost mixture, the DEHP biodegradation efficiency was 99% after 35 days. The highest degradation efficiency was recorded at the thermophilic phase (day 3 - day 11) with the biodegradation rate reached 187 mg kg −1 day −1 . DEHP was metabolized to dibutyl phthalate (DBP) and dimethyl phthalate (DMP) and would be oxidized to benzyl alcohol (BA) and mineralized into CO2 and water via various metabolisms. Finally, the compost's quality with residual DEHP was evaluated using Brassica chinensis L. seeds via 96 h of germination tests. The compost (at day 35) with a trace amount of DEHP as the end product showed no significant effect on the germination rate of Brassica chinensis L. seeds (88%) compared to that without DEHP (94%), indicating that the compost can be reused as fertilizer in agricultural applications. These results provide an improved understanding of the DEHP biodegradation via food waste composting without bioaugmentation and hence facilitating its green remediation and conversion into value-added products. Nevertheless, further studies are needed on DEHP biodegradation in large-scale food waste composting or industrial applications.